Surgical pathology of the thyroid gland - Oré, Juan (2008)
Introduction: Due to the great diversity and variety of thyroid surgical pathology in our country, we review our experience with this pathology. Objectives: To determine the incidence of thyroid gland surgical pathology in patients undergoing surgery. Design: Descriptive and retrospective study. Setting: Head and neck service, Hospital Dos de Mayo, Lima, Peru, a teaching hospital. Participants: Patients undergoing surgery of the thyroid gland. Interventions: Clinical histories and surgical reports involving the thyroid gland in the period January 1997 through December 2006 were reviewed. Main outcome measures: Pathology results of thyroid gland surgical specimens. Results: Two hundred and seventy four cases had thyroid surgery, 81,4% females; 56,9% of the cases corresponded to Lima, capital of Peru. Incidence was higher between 30 and 59 years of age. Growing tumor was the most frequent sign with 97,8%. Total thyroidectomy was the most frequent surgery (39,8%). Benign pathologies represented 58% of the cases, with follicular adenoma as the main pathology (23%); and for malignant tumors (42% from the total) papillary carcinoma was the main neoplasia (23,7%). Conclusions: Surgical pathology of the thyroid gland had higher incidence in women, mainly in the 4th, 5th and 6th age decades. Thyroid tumors were by far benign and the main malignant tumor was papillary carcinoma. Fine needle aspiration biopsy continues to be the most important auxiliary study in the patient with a thyroid tumor, with high specificity value (97,7) and positive predictive value (95,4).